Pengaruh Kualitas Produk Dan Saluran Distribusi Terhadap Keputusan Pembelian Produk Sari Nanas Segar Studi Kasus Konsumen PT Putra Jaya Nanas Desa Sidorejo Kecamatan Ponggok Kabupaten Blitar - Tommy Febriyanto; Diana Ambarwati (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
This study is to determine the effect of product quality and distribution channels on purchasing decisions at PT Putra Jaya Nanas Blitar. Types of quantitative research. Data collrction techniques primary data and secondary data, the number of samples is 100 responden at PT Putra Jaya Nanas Blitar. The analysis techniques are Validity Test, F Test and Coefficient of Determination Test. The result of multiple linier regression research Y= 4,430 + 0,316X1 + 0,792X2 and the result of the t-test of product quality variables have a significant effect on purchasing decisions. Distribution channels have a significant effect on purchasing decisions the result of the F test obtained the result of Fcount with a significance value of 0,000<0,05.